ADAPTABILITY OF FOOD CROP FARMERS TO WEATHER CHANGES IN NORTH CENTRAL TIMOR REGENCY - Nabuasa, Mirna; Sipayung, Boanerges; Falo, Marsianus; Matoneng, Ody (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
The adaptability of food crop farmers is the key to food security. North Central Timor Regency, which is one of the food crop centers in the border area between Indonesia and the Democratic Republic of Timor Leste, has experienced a decline in food crop production. The purpose of this study was to analyze factors influencing food crop production and the adaptability of food crop farmers in North Central Timor Regency. This study used quantitative analysis with Ordinary Least Square (OLS) analysis using the Cobb Douglass approach and multinominal logistic regression. The results showed that planting area affected food crop production. Food crop farmers need intensive assistance in dealing with weather changes. Farmers' knowledge and independence reduce the opportunities for farmers' adaptability.